The punishment of slaves in Early Christianity: the views of some selected Church Fathers - C. L. de Wet (Acta Theologica)
With few exceptions, many of the Church Fathers approved, in principle, of the punishment of slaves. However, there were very specific guidelines on why, how, and when to punish slaves. The purpose of this article is to analyse more closely how some of the early Church Fathers conceptualised the punishment of slaves. The study begins, first, by examining the theological justifications for the punishment of slaves. Secondly, it assesses the reasons for punishment – for what reasons did these Church Fathers admonish their slaveholding audiences to punish their slaves? Thirdly, the author investigates some selected Church Fathers’ advice on how to punish, in terms of both the psychological disposition of the owner and the various methods for punishment directed towards the slave body. Finally, the article more specifically explores how these Church Fathers understood some of the main elements that were present in, during, and after punishment, namely fear and pain.